2019
DOI: 10.22219/jpbi.v5i1.7262
|View full text |Cite
|
Sign up to set email alerts
|

Using critical analysis to develop metacognitive ability and critical thinking skills in biology

Abstract: Possessing and developing metacognitive abilities are an essential part of the learning process. This study is a class action research on the use of critical analysis to identify its influence on students’ metacognitive abilities and critical thinking skills as well as to discover the relationship between metacognitive abilities and critical thinking skills. The sample of this study is 76 students from 217 students taking cell biology and non-vascular plants subject during the fall semester. It is a descriptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 32 publications
0
14
0
1
Order By: Relevance
“…Based on several previous studies, various learning models and strategies are reported to be able to empower metacognition optimally. Some of these learning models and strategies, including problem-based learning (Haryani et al, 2018;Kevin, 2011;Kuvac & Koc, 2018;Siagian, Saragih, & Sinaga, 2019), projectbased learning (Husamah, 2015;Sart, 2014;Tumewu, Wulan, & Sanjaya, 2017), learning with learning-journal implementing (Nurajizah et al, 2018), using critical analysis (Lukitasari, Hasan, & Murtafiah, 2019), classroombased learning communities and self-assessment (Siegesmund, 2016), learning with self and peer assessment (Pantiwati & Husamah, 2017), and inquiry-based learning (Nunaki et al, 2019). In addition to the application of these various learning models, teachers must also implement an assessment process that supports the improvement of students' metacognition.…”
Section: Resultsmentioning
confidence: 99%
“…Based on several previous studies, various learning models and strategies are reported to be able to empower metacognition optimally. Some of these learning models and strategies, including problem-based learning (Haryani et al, 2018;Kevin, 2011;Kuvac & Koc, 2018;Siagian, Saragih, & Sinaga, 2019), projectbased learning (Husamah, 2015;Sart, 2014;Tumewu, Wulan, & Sanjaya, 2017), learning with learning-journal implementing (Nurajizah et al, 2018), using critical analysis (Lukitasari, Hasan, & Murtafiah, 2019), classroombased learning communities and self-assessment (Siegesmund, 2016), learning with self and peer assessment (Pantiwati & Husamah, 2017), and inquiry-based learning (Nunaki et al, 2019). In addition to the application of these various learning models, teachers must also implement an assessment process that supports the improvement of students' metacognition.…”
Section: Resultsmentioning
confidence: 99%
“…Another study conducted by Semerci and Elaldi (2014) revealed that there is a positive significant relationship between metacognitive beliefs and critical thinking skills, but the relationship can be considered as lower than moderate level. Lukitasari, Hasan and Murtafiah (2019) explored the relationship between metacognitive abilities and critical thinking skills by sampling 76 students who study in the Department of Biology Education, Indonesia and unearthed that there is a strong positive relationship between the two structures. Based on these results, it can be concluded that the development of students' critical thinking skills contributes to the development of their metacognitive thinking skills.…”
Section: Discussionmentioning
confidence: 99%
“…also use the CTS indicator from Ennis, which consists of providing a simple explanation, developing basic skills, drawing conclusions, providing a further explanation, and setting strategies and tactics (Lukitasari, Purnamasari, et al, 2019). In the same year, used the CTS indicator from Avierkieva (2015) and Arifin (2012), which consisted of grammar, completeness, the consistency of information presented, creativity, defining, and developing information (Lukitasari, Hasan, & Murtafiah, 2019). In contrast to Maryuningsih (2019), who uses the CTS indicator from Facione, which consists of interpretations, analyzes, evaluations, inferences, and explanations that produce a score of 57.49.…”
Section: Instrumentsmentioning
confidence: 99%